A high-barrier five-layer structure infusion film and a preparation method thereof
Patent Information
- Application Number
- CN202610901284.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-27
AI Technical Summary
但由于 COP 与 PP、PE 的极性差异显著,直接进行共挤复合时极易出现层间剥离分层现象
(1) 双层协同高阻隔,省去外置阻隔袋
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to a film for packaging intravenous infusion drugs, specifically a high-barrier five-layer infusion film. Background Technology
[0002] Non-PVC multilayer co-extruded film, as the mainstream packaging material for large-capacity infusion bags, must meet pharmacopoeia and YBB national standards, such as withstanding 121℃ high-temperature sterilization, possessing high light transmittance, and good gas barrier properties. Currently, commercially available five-layer infusion membranes mostly use polyolefin blends such as polypropylene (PP) and polyethylene (PE) as the middle barrier layer. However, the water and oxygen barrier capabilities of polyolefins themselves are limited; the water vapor transmission rate of conventional products is between 2.5 and 3.0 g / (m³). 2 • 24h range, oxygen permeability is 800-1100 cm⁻¹ 3 / (m 2 The pressure (0.1 MPa) is insufficient to meet the long-term storage requirements of easily oxidized and hygroscopic drugs such as amino acids, vitamins, and anti-tumor drugs.
[0003] Currently, the industry's conventional solution is to add a separate high-barrier outer bag to the infusion bag. However, this additional packaging process increases production costs, and manual unpacking is required during clinical medication preparation. Furthermore, the corners of the outer bag are prone to air and water leakage, failing to fundamentally address the shortcomings in the membrane's barrier performance. Adding inorganic fillers to polyolefins to improve barrier performance can lead to decreased film transmittance and may cause solid particles to precipitate, contaminating the medication, thus failing to meet safety standards for pharmaceutical packaging materials.
[0004] Cyclic olefin polymers (COPs) possess extremely low water and oxygen permeability coefficients, making them high-barrier pharmaceutical raw materials. However, due to the significant polarity difference between COPs and PP and PE, interlayer delamination is highly likely to occur during direct co-extrusion. Ester polymers (PETGs) combine high barrier properties with excellent surface abrasion and heat resistance; however, PETGs also suffer from poor interfacial compatibility with PE and COPs. Current technologies lack a suitable transitional bonding system, making it impossible to achieve adhesive-free five-layer integrated co-extrusion of polypropylene (PP), cyclic olefin polymers (COPs), polyethylene (PE), and polyethylene terephthalate-1,4-cyclohexanedimethyl ester (PETG).
[0005] In view of the above, this invention proposes a novel high-barrier five-layer infusion membrane. By adjusting the raw material ratio of each layer and designing the structure, a cyclic olefin polymer with superior barrier properties is selected as the intermediate barrier layer. Simultaneously, compatible grafting materials are used in each layer to enhance interlayer bonding. Without the need for additional adhesives, a high-performance infusion membrane can be obtained through a single extrusion molding process. This membrane improves barrier performance from the membrane material itself, eliminating the need for an additional outer barrier bag. This simplifies the packaging process, reduces packaging costs, and better meets the storage requirements of infusion products with high stability requirements, ensuring the quality stability of the medication within its shelf life. Summary of the Invention To address the aforementioned problems, this invention provides a high-barrier five-layer infusion membrane. This membrane possesses advantages such as being non-toxic, resistant to boiling, highly transparent, and highly barrier.
[0006] The high-barrier five-layer infusion membrane of the present invention is a five-layer composite membrane, which is composed of the following from the inner layer to the outer layer: PP+SEBS, MAH-g-PP+PP, COP, MAH-g-PE+PE, and PETG.
[0007] The inner layer is composed of the following raw materials in the following mass percentages: 70%~80% polypropylene, 20%~30% SEBS, and has a thickness of 30~50μm.
[0008] The innermost layer is composed of the following raw materials by mass percentage: MAH-g-PP 50%~70%, polypropylene 30%~50%, with a thickness of 10~20μm.
[0009] The intermediate layer is composed of the following raw materials by mass percentage: 100% cyclic olefin polymer, with a thickness of 20~50μm.
[0010] The outermost layer is composed of the following raw materials in the following mass percentages: PE 40%~60%, MAH-g-PE 20%~40%, E-GMA 10%~20%, with a thickness of 70~130μm.
[0011] The outer layer is composed of the following raw materials by mass percentage: 100% ester copolymer (PETG) with a thickness of 10~30μm.
[0012] The polypropylene used in the inner layer of the high-barrier five-layer infusion membrane has a melting point between 115 and 135°C and a density of 0.87 to 0.92 g / cm³. 3 The melt index (230℃ / 2.16 kg) is 6.0~9.0 g / 10min; SEBS elastomer, melting point between 90~150℃, density 0.89~0.92 g / cm³. 3The melt index (190℃ / 2.16 kg) is 2.0~8.0 g / 10min. The main function of this layer is to provide good drug compatibility and a wide heat sealing temperature range.
[0013] The MAH-g-PP used in the innermost layer of the high-barrier five-layer infusion membrane has a melting point between 130 and 150°C and a density of 0.88 to 0.92 g / cm³. 3 Melt index (190℃ / 2.16 kg) is 2.0~4.0 g / 10min; polypropylene has a melting point between 120~140℃ and a density of 0.87~0.92 g / cm³. 3 The melt flow index (230℃ / 2.16 kg) is 4.0~7.0 g / 10min. The main function of this layer is to solve the problem of insufficient adhesion due to the large polarity difference between the inner polypropylene layer and the middle cyclic olefin polymer. As an adhesive layer, it enhances the composite strength between the two layers and ensures the overall structural stability of the membrane material.
[0014] The cyclic olefin polymer used in the intermediate layer of the high-barrier five-layer infusion membrane has a melting point between 60 and 150°C and a density of 1.01 to 1.02 g / cm³. 3 The melt index (230℃ / 2.16 kg) is 9.0~20.0 g / 10min. The cyclic olefin polymer itself has extremely low oxygen and water vapor permeability. As the core barrier layer of this invention, it can significantly improve the overall barrier performance of the membrane material without the need for additional barrier fillers, thus avoiding the impact of fillers on the light transmittance and hygiene safety of the membrane material.
[0015] The polyethylene used in the outermost layer of the high-barrier five-layer infusion membrane has a melting point between 100 and 120°C and a density of 0.90 to 0.92 g / cm³. 3 The melt flow index (190℃ / 2.16 kg) is 0.5~3.0 g / 10min; the MAH-g-PE used has a melting point between 90~150℃ and a density of 0.90~0.92 g / cm³. 3 The melt flow index (190℃ / 2.16 kg) is 1.0~3.0 g / 10min; the E-GMA used has a melting point between 90~100℃ and a density of 0.90~0.95 g / cm³. 3 The melt flow index (190℃ / 2.16 kg) is 1.0~3.0 g / 10 min. This layer also serves as a bonding layer, enhancing the adhesion between the intermediate cyclic olefin polymer barrier layer and the outer structure, thus ensuring the overall composite stability.
[0016] The ester copolymer used in the outer layer of the high-barrier five-layer infusion membrane has a melting point between 200 and 210°C and a density of 1.02 to 1.18 g / cm³. 3The melt flow index (230℃ / 2.16 kg) is 12~25 g / 10min. The main function of this layer is to provide the membrane material with good mechanical strength and heat resistance.
[0017] The cyclic olefin polymer is one or more combinations of ZEONEX 5000, ZEONEX 690R, TOPAS 8007 or TOPAS 6013.
[0018] The total thickness of the five-layer membrane is 200~250μm.
[0019] This invention also provides a method for preparing a high-barrier five-layer infusion membrane, comprising the following steps: Step 1: The raw materials in the inner layer, the second inner layer, the middle layer, the second outer layer and the outer layer are respectively drawn into the extruder hopper. The feed screw of the hopper feeds according to the preset mass percentage, and the corresponding plastic particles are conveyed to the mixing hopper. After being mixed evenly, they are sent to the corresponding heating section of the extruder. By controlling the heating temperature of each section of the extruder, the plastic particles are fully melted and plasticized to obtain the molten mixture of each layer. Step 2: The plasticized molten mixture of each layer is filtered through a filter screen to remove impurities, and then transported to the die head for extrusion through a connecting pipe. The speed of each extruder is controlled, and the five-layer structure is laminated into one piece at the die according to the preset thickness to obtain a five-layer film. Subsequently, a planar superimposed die head is used to complete the lamination. The temperature of the planar superimposed die head is controlled at 200~235℃. After extrusion, clean air forms a downblown film bubble, and the blow-up ratio is controlled between 1.0 and 2.0. The blowing pressure is 0.4MPa~0.8MPa. Clean air and purified water are used to cool the film bubble, and the cooling water temperature is controlled at 15℃~30℃ and the flow rate is 500L / h~2000L / h. After the film bubble is cooled and flattened, it is sent to the winding machine to complete the winding.
[0020] In step 1, the heating temperature control of each extruder is as follows: outer layer extruder: preheating stage 50~60℃, melting stage 190~220℃, heat preservation stage 210~230℃; second outer layer extruder: preheating stage 50~60℃, melting stage 190~210℃, heat preservation stage 200~220℃; middle layer extruder: preheating stage 50~80℃, melting stage 210~230℃, heat preservation stage 220~230℃; second inner layer extruder: preheating stage 50~60℃, melting stage 190~210℃, heat preservation stage 210~230℃; inner layer extruder: preheating stage 50~60℃, melting stage 190~210℃, heat preservation stage 210~230℃.
[0021] In step 2, the speed control of each extruder is as follows: outer layer extruder 20~50 rpm, secondary outer layer extruder 40~80 rpm, middle layer extruder 20~50 rpm, secondary inner layer extruder 10~40 rpm, and inner layer extruder 20~50 rpm.
[0022] Compared with existing multilayer infusion membranes, the beneficial effects of the present invention are as follows: (1) Double-layer synergistic high barrier, eliminating the need for an external barrier bag The intermediate layer is a composite of two high-barrier substrates: a fully cyclic olefin polymer (COP) and an outer ester copolymer (PETG), requiring no inorganic fillers. The finished product has a water vapor permeability ≤1.1 g / (m²). (24h); Compared with traditional polyolefin interlayer infusion membranes, the water vapor barrier performance is improved by more than 50%, the oxygen barrier performance by more than 40%, and the nitrogen barrier performance by more than 60%. Its barrier performance exceeds the index of conventional external barrier bags, eliminating the need for outer packaging bags and thus reducing production and clinical costs.
[0023] (2) Differentiated grafting on both sides effectively prevents delamination. The innermost layer uses maleic anhydride-grafted polypropylene (MAH-g-PP) to facilitate the interfacial bonding between polypropylene (PP) and cyclic olefin polymers (COP). The outermost layer uses methacrylate-grafted polyethylene and maleic anhydride-grafted polyethylene (MAH-g-PE) to facilitate the interfacial bonding between cyclic olefin polymers (COP), polyethylene (PE), and ester copolymers (PETG). This effectively solves the problem of polarity incompatibility between cyclic olefin polymers (COP) and polypropylene (PP) / polyethylene (PE) / ester copolymers (PETG). The entire film uses no adhesives and exhibits no delamination after sterilization at 121°C and tensile testing, demonstrating excellent structural stability.
[0024] (3) The process has good versatility and is convenient for mass production. The entire process employs a five-layer simultaneous co-extrusion blow molding process, which is compatible with existing five-layer co-extrusion blown film equipment. The extrusion temperature and speed parameters of each layer are matched with the raw material processing characteristics, resulting in a shorter production process and good industrial adaptability. Detailed Implementation The embodiments of the present invention will be described in detail below with reference to the examples. The following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.
[0025] The method for preparing the five-layer infusion membrane provided by this invention is as follows: Step 1: The raw materials of each layer are respectively pumped into the extruder hopper. The feed screw of the hopper feeds the plastic particles by the preset mass percentage and conveys them to the mixing hopper. After mixing, the particles enter the heating sections of the extruder. The plastic particles are melted and plasticized by controlling the heating temperature of each section of the extruder to obtain molten mixtures. Step 2: The fully plasticized molten mixture is filtered through a filter screen to remove impurities, and then extruded through a connecting pipe and a die head. The speed of the extruder is controlled separately, and the five layers are laminated together at the die to form a five-layer film.
[0026] In step 1, the heating temperatures of the outer extruder are as follows: preheating temperature 50~60℃, melting temperature 190~220℃, and holding temperature 210~230℃. The heating temperatures for the secondary outer layer extruder are: preheating temperature 50~60℃, melting temperature 190~210℃, and holding temperature 200~220℃. The heating temperature of the intermediate layer extruder is: preheating temperature 50~80℃, melting temperature 210~230℃, and holding temperature 220~230℃; The heating temperature for the inner layer extruder is: preheating temperature 50~60℃, melting temperature 190~210℃, and holding temperature 210~230℃. The heating temperatures for the inner extruder are: preheating temperature 50~60℃, melting temperature 190~210℃, and holding temperature 210~230℃.
[0027] The specific control of the extruder speeds in step 2 is as follows: outer layer extruder: 20~50 rpm, second outer layer extruder: 40~80 rpm, middle layer extruder: 20~50 rpm, second inner layer extruder: 10~40 rpm, inner layer extruder: 20~50 rpm.
[0028] The raw material is extruded by the screw of the extruder and then redistributed through the die head. The die head temperature is 200~235℃. A planar superimposed die head is used. After extrusion through the die head, clean air forms a downblown film bubble with a blow-up ratio between 1.0 and 2.0, a blowing pressure of 0.4MPa~0.8MPa, a cooling water temperature of 15℃~30℃, and a flow rate of 500L / h~2000L / h. The film bubble is cooled by clean air and purified water, folded flat, and then enters the winding machine for winding.
[0029] Examples 1-4 The outer layer, with a thickness of 10~30μm, is composed of the following raw materials in the following mass percentages: 100% ester copolymer PETG; wherein the melt flow rate of the ester copolymer at 230℃ / 2.16Kg, as measured according to GB-T3682, is 18g / 10min. The outermost layer, with a thickness of 70~130μm, is composed of the following raw materials in the following mass percentages: polyethylene 40%, MAH-g-PE 40%, and E-GMA 20%; wherein the melt flow rate of polyethylene at 190℃ / 2.16Kg, as measured according to GB-T3682, is 1.0g / 10min; the melt flow rate of MAH-g-PE at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min; and the melt flow rate of E-GMA at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min. The intermediate layer, with a thickness of 20~50μm, is composed of the following raw materials by mass percentage: 100% cyclic olefin polymer, which is a blend of ZEONEX 5000 and ZEONEX 690R in a ratio of 2:1. The innermost layer, with a thickness of 10~20μm, is composed of the following raw materials in the following mass percentages: MAH-g-PP 70% and polypropylene 30%; wherein the melt flow rate of MAH-g-PP at 230℃ / 2.16Kg, as measured according to GB-T3682, is 2.5g / 10min, and the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 5.5g / 10min. The inner layer, with a thickness of 30~50μm, is composed of the following raw materials in the following mass percentages: 80% polypropylene and 20% SEBS; wherein the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 7.0g / 10min, and the melt flow rate of SEBS at 230℃ / 2.16Kg, as measured according to GB-T3682, is 4.0g / 10min.
[0030] The specific implementation details are shown in Table 1.
[0031] Table 1 Thickness of each layer in Examples 1-4
[0032] Comparative Examples 1-2 The outer layer, with a thickness of 10~30μm, is composed of the following raw materials in the following mass percentages: 100% ester copolymer; wherein the melt flow rate of the ester copolymer at 230℃ / 2.16Kg, as measured according to GB-T3682, is 18g / 10min. The outermost layer, with a thickness of 70~130μm, is composed of the following raw materials in the following mass percentages: polyethylene 40%, MAH-g-PE 40%, and E-GMA 20%; wherein the melt flow rate of polyethylene at 190℃ / 2.16Kg, as measured according to GB-T3682, is 1.0g / 10min; the melt flow rate of MAH-g-PE at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min; and the melt flow rate of E-GMA at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min. The intermediate layer, with a thickness of 20~50μm, is composed of the following raw materials by mass percentage: 100% cyclic olefin polymer, which is a blend of ZEONEX 5000 and ZEONEX 690R in a ratio of 2:1. The innermost layer, with a thickness of 10~20μm, is composed of the following raw materials in the following mass percentages: MAH-g-PP 70% and polypropylene 30%; wherein the melt flow rate of MAH-g-PP at 230℃ / 2.16Kg, as measured according to GB-T3682, is 2.5g / 10min, and the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 5.5g / 10min. The inner layer, with a thickness of 30~50μm, is composed of the following raw materials in the following mass percentages: 80% polypropylene and 20% SEBS; wherein the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 7.0g / 10min, and the melt flow rate of SEBS at 230℃ / 2.16Kg, as measured according to GB-T3682, is 4.0g / 10min.
[0033] The specific implementation details are shown in Table 2.
[0034] Table 2 Thickness of each layer in Comparative Examples 1-2
[0035] Comparative Examples 3-4 The outer layer, with a thickness of 10~30μm, is composed of the following raw materials in the following mass percentages: 100% ester copolymer; wherein the melt flow rate of the ester copolymer at 230℃ / 2.16Kg, as measured according to GB-T3682, is 18g / 10min. The outermost layer, with a thickness of 70~130μm, is composed of the following raw materials in the following mass percentages: 80% polyethylene, 10% MAH-g-PE, and 10% E-GMA; wherein the melt flow rate of polyethylene at 190℃ / 2.16Kg, as measured according to GB-T3682, is 1.0g / 10min; the melt flow rate of MAH-g-PE at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min; and the melt flow rate of E-GMA at 190℃ / 2.16Kg, as measured according to GB-T3682, is 2.0g / 10min. The intermediate layer, with a thickness of 20~50μm, is composed of the following raw materials by mass percentage: 100% cyclic olefin polymer, which is a blend of ZEONEX 5000 and ZEONEX 690R in a ratio of 2:1. The innermost layer, with a thickness of 10~20μm, is composed of the following raw materials in the following mass percentages: 70% polypropylene and 30% MAH-g-PP; wherein the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 5.5g / 10min, and the melt flow rate of MAH-g-PP at 230℃ / 2.16Kg, as measured according to GB-T3682, is 2.5g / 10min. The inner layer, with a thickness of 30~50μm, is composed of the following raw materials in the following mass percentages: 80% polypropylene and 20% SEBS; wherein the melt flow rate of polypropylene at 230℃ / 2.16Kg, as measured according to GB-T3682, is 7.0g / 10min, and the melt flow rate of SEBS at 230℃ / 2.16Kg, as measured according to GB-T3682, is 4.0g / 10min.
[0036] The specific implementation details are shown in Table 3.
[0037] Table 3 Thickness of each layer in Comparative Examples 3-4
[0038] Comparative Example 5 The materials and proportions of each layer are the same as in Examples 1-4. The thickness of each layer is the same as in Example 1. The intermediate layer is made of H171B material from Kuraray, a leading EVOH manufacturer, which has better barrier properties than PP and PE. The proportion of H171B is 100%.
[0039] Comparative Example 6 The materials and proportions of each layer are the same as in Examples 1-4. The thickness of each layer is the same as in Example 1. The intermediate layer is made of 100% C40 material from BASF, a nylon head manufacturer, which has better barrier properties than PP and PE. The proportion of C40 is 100%.
[0040] The performance of the film was tested according to the national standard YBB00112005-2015. All relevant samples underwent water bath sterilization treatment under the following conditions: temperature 121℃, holding time 30min. The relevant performance is shown in Tables 4 and 5.
[0041] Table 4. Thin film performance test structures of Examples 1-4
[0042] Table 5. Test structures for thin film performance of Comparative Examples 1-4
[0043] Note: (1) Since the interlayer peel strength cannot be directly measured, the interlayer stability test is conducted according to the tensile strength test. Because different materials have different elongation at break, if the interlayer stability is insufficient and the interlayer adhesion is insufficient during tensile testing, delamination will occur. (2) If delamination occurs, the film layer with the lower elongation at break will break first. In the test, the elongation at break is calculated based on the elongation at the time of breakage. For the technical requirements of elongation at break, please refer to the commonly used control requirements in the industry. (3) The gas permeation rate of traditional co-extruded membranes for infusion is: water vapor permeation rate: 2.5~3.0 g / (m³). 2 • 24h), oxygen permeability: 800~1100cm³ 3 / (m 2 • 24h • 0.1MPa), nitrogen permeation rate: 250~350cm 3 / (m 2 ·24h·0.1MPa).
[0044] Examples 1-4 are preferred embodiments of the present invention, and their main performance indicators all meet YBB and industry requirements. The gas permeation rate is significantly reduced compared to traditional infusion membranes, indicating a substantial improvement in barrier performance. Furthermore, the thicker the cyclic olefin polymer layer, the greater the improvement in barrier performance. Compared to conventional infusion membranes, Example 1 shows a 56% improvement in water vapor permeation barrier performance, a 41% improvement in oxygen barrier performance, and a 60% improvement in nitrogen barrier performance; Example 4 shows a 76% improvement in water vapor permeation barrier performance, a 55% improvement in oxygen barrier performance, and a 78% improvement in nitrogen barrier performance.
[0045] Comparative Example 1 has a thinner cyclic olefin polymer layer than Example 1. When the cyclic olefin polymer layer is too thin, the barrier performance is not significantly different from that of traditional infusion membranes. Comparative Example 2 has a thicker cyclic olefin polymer layer than Example 4. When the cyclic olefin polymer layer is too thick, the barrier performance is also improved, but the elongation at break is lower than the commonly used control requirements in the industry.
[0046] Compared with Example 1 and Example 4, Comparative Example 3 and Comparative Example 4 did not add maleic anhydride grafting material to the inner and outer layers. The membrane material without MAH-g-PP is prone to delamination, that is, the interlayer peel strength is insufficient, the interlayer adhesion is insufficient, and the interlayer stability is poor.
[0047] Comparative Examples 5 and 6 attempted EVOH and PA materials with equally excellent barrier properties, but neither of these materials could withstand 121°C moist heat sterilization. After moist heat sterilization, the light transmittance was extremely poor, and the barrier properties of EVOH were significantly reduced due to the effects of moist heat sterilization.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-barrier five-layer infusion membrane, characterized in that, It has a five-layer structure, from the inside out: inner layer, second inner layer, middle layer, second outer layer, and outer layer; by mass percentage, The inner layer is made of 70%~80% polypropylene (PP) and 20%~30% styrene-ethylene-butene-styrene block copolymer (SEBS), with a thickness of 30~50μm. The innermost layer is made of maleic anhydride-grafted polypropylene MAH-g-PP 50%~70% and polypropylene PP 30%~50%, with a thickness of 10~20μm; The intermediate layer is made of cyclic olefin polymer with a COP of 100% and a thickness of 20~50μm; The outermost layer is made of polyethylene (PE) 40%~60%, maleic anhydride-grafted polyethylene (MAH-g-PE) 20%~40%, and methacrylate-grafted polyethylene (E-GMA) 10%~20%, with a thickness of 70~130μm. The outer layer material is 100% ester copolymer PETG, with a thickness of 10~30μm.
2. The high-barrier five-layer infusion membrane according to claim 1, characterized in that, The inner layer uses polypropylene with a melting point of 115~135℃ and a density of 0.87~0.92 g / cm³. 3 The melt index at 230℃ / 2.16 kg is 6.0~9.0 g / 10 min; The polypropylene used in the inner layer has a melting point of 120~140℃ and a density of 0.87~0.92 g / cm³. 3 The melt index at 230℃ / 2.16 kg is 4.0~7.0 g / 10 min; The cyclic olefin polymer used in the intermediate layer has a melting point of 60~150℃ and a density of 1.01~1.02 g / cm³. 3 At 230℃ and 2.16 kg, the melt index is 9.0~20.0 g / 10 min; The polyethylene used in the outermost layer has a melting point of 100~120℃ and a density of 0.90~0.92 g / cm³. 3 The melt index at 190℃ / 2.16 kg is 0.5~3.0 g / 10 min.
3. The high-barrier five-layer infusion membrane according to claim 1, characterized in that, The outer layer uses an ester copolymer with a melting point of 200~210℃ and a density of 1.02~1.18 g / cm³. 3 The melt index is 12~25g / 10min at 230℃ / 2.16 kg.
4. The high-barrier five-layer infusion membrane according to claim 1, characterized in that, The MAH-g-PP has a melting point of 130~150℃ and a density of 0.88~0.92 g / cm³. 3 At 230℃ and 2.16 kg, the melt index is 2.0~4.0 g / 10 min; The MAH-g-PE has a melting point of 90~150℃ and a density of 0.90~0.92 g / cm³. 3 At 190℃ / 2.16 kg, the melt index is 1.0~3.0 g / 10 min; The E-GMA has a melting point of 80~100℃ and a density of 0.90~0.95 g / cm³. 3 The melt index is 1.0~3.0 g / 10 min at 190℃ / 2.16 kg.
5. The high-barrier five-layer infusion membrane according to claim 1, characterized in that, The SEBS has a melting point of 90~150℃ and a density of 0.89~0.92 g / cm³. 3 The melt index is 2.0~8.0 g / 10 min at 230℃ / 2.16 kg.
6. The high-barrier five-layer infusion membrane according to claim 1, characterized in that, The cyclic olefin polymer is one or more combinations of ZEONEX 5000, ZEONEX 690R, TOPAS 8007 or TOPAS 6013.
7. A method for preparing a high-barrier five-layer infusion membrane, characterized in that, Includes the following steps: Step 1: The raw materials of the inner layer, the second inner layer, the middle layer, the second outer layer and the outer layer are respectively drawn into the material bins of each extruder. The feed screw of the material bin feeds the plastic particles by the preset mass percentage and conveys them to the mixing hopper. After mixing, they enter the heating sections of the extruder. By controlling the heating temperature of each section of the extruder, the plastic particles are melted and plasticized to obtain molten mixtures. Step 2: The fully plasticized molten mixture is filtered through a filter screen to remove impurities. At the same time, it is extruded through a connecting pipe and a die head. The speed of the extruder is controlled separately, and the five layers are laminated together at the die head according to the preset thickness to form a five-layer film.
8. The method for preparing a high-barrier five-layer infusion membrane according to claim 7, characterized in that, In step 1, the heating temperature of the outer extruder is: 50~60℃ in the preheating stage, 190~220℃ in the melting stage, and 210~230℃ in the heat preservation stage; The heating temperature of the secondary outer layer extruder is: 50~60℃ in the preheating stage, 190~210℃ in the melting stage, and 200~220℃ in the heat preservation stage; The heating temperature of the intermediate layer extruder is: 50~80℃ in the preheating stage, 210~230℃ in the melting stage, and 220~230℃ in the heat preservation stage. The heating temperature of the inner layer extruder is: 50~60℃ in the preheating stage, 190~210℃ in the melting stage, and 210~230℃ in the heat preservation stage. The heating temperature of the inner extruder is as follows: 50~60℃ in the preheating stage, 190~210℃ in the melting stage, and 210~230℃ in the heat preservation stage.
9. The method for preparing a high-barrier five-layer infusion membrane according to claim 8, characterized in that, The specific control of the extruder speeds in step 2 is as follows: outer layer extruder: 20~50 rpm, second outer layer extruder: 40~80 rpm, middle layer extruder: 20~50 rpm, second inner layer extruder: 10~40 rpm, inner layer extruder: 20~50 rpm.
10. The method for preparing a high-barrier five-layer infusion membrane according to claim 8, characterized in that, Five layers are laminated together using a planar superimposed die. The temperature of the planar superimposed die is 200~235℃. After extrusion through the planar superimposed die, clean air forms a downblown film bubble with a blow-up ratio between 1.0 and 2.0, an air pressure of 0.4MPa~0.8MPa, a cooling water temperature of 15℃~30℃, and a flow rate of 500L / h~2000L / h. The film bubble is cooled by clean air and purified water, folded flat, and then wound up by a winding machine.